Virtual Reality Laboratory Laws of Inheritance Enhancing Students' Technological Literacy - Fahmi, M Iqbal Najib; Zubaidah, Siti; Mahanal, Susriyati; Setiawan, Deny (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The lack of introduction and habituation to using interactive media in learning can cause students to have low technological literacy. Virtual reality technology can help us learn the law of inheritance of traits. This research aims to develop learning media using virtual reality technology that is valid, practical, and effective in improving students’ technological literacy. The stages we carried out refer to the development model of William W. Lee and Diana L. Owens. Media feasibility is based on the results of material validation, media, small group trials, and media implementation to high school students. Technological literacy was measured using a questionnaire and observation sheet. The subjects consisted of 127 students taking the material on the law of Inheritance of Traits. The results of the study obtained a material validation percentage of 100% (very valid), media validation of 89% (valid), and small group trials of 90% (very practical). The results of the virtual reality laboratory effectiveness test show the significance value of the ANCOVA test of 0.000 is smaller than α (α = 0.05). These results indicate that the developed media are valid, practical, and effective for improving students’ technological literacy in learning the law of Inheritance of Traits.